If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6p + 7q)(-2p + 10q) = 0 Multiply (6p + 7q) * (-2p + 10q) (6p * (-2p + 10q) + 7q * (-2p + 10q)) = 0 ((-2p * 6p + 10q * 6p) + 7q * (-2p + 10q)) = 0 Reorder the terms: ((60pq + -12p2) + 7q * (-2p + 10q)) = 0 ((60pq + -12p2) + 7q * (-2p + 10q)) = 0 (60pq + -12p2 + (-2p * 7q + 10q * 7q)) = 0 (60pq + -12p2 + (-14pq + 70q2)) = 0 Reorder the terms: (60pq + -14pq + -12p2 + 70q2) = 0 Combine like terms: 60pq + -14pq = 46pq (46pq + -12p2 + 70q2) = 0 Solving 46pq + -12p2 + 70q2 = 0 Solving for variable 'p'. Factor out the Greatest Common Factor (GCF), '2'. 2(23pq + -6p2 + 35q2) = 0 Factor a trinomial. 2((-6p + -7q)(p + -5q)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-6p + -7q)' equal to zero and attempt to solve: Simplifying -6p + -7q = 0 Solving -6p + -7q = 0 Move all terms containing p to the left, all other terms to the right. Add '7q' to each side of the equation. -6p + -7q + 7q = 0 + 7q Combine like terms: -7q + 7q = 0 -6p + 0 = 0 + 7q -6p = 0 + 7q Remove the zero: -6p = 7q Divide each side by '-6'. p = -1.166666667q Simplifying p = -1.166666667qSubproblem 2
Set the factor '(p + -5q)' equal to zero and attempt to solve: Simplifying p + -5q = 0 Solving p + -5q = 0 Move all terms containing p to the left, all other terms to the right. Add '5q' to each side of the equation. p + -5q + 5q = 0 + 5q Combine like terms: -5q + 5q = 0 p + 0 = 0 + 5q p = 0 + 5q Remove the zero: p = 5q Simplifying p = 5qSolution
p = {-1.166666667q, 5q}
| 8n^2-18N-5=0 | | 3(C-D)D= | | p^2-15p+50=0 | | (4u+9)(1-u)=0 | | 7/8a-5/3a | | 8n-(5n+4)=17 | | x^1/2=13 | | (4u+9)(1-0)=0 | | 5y-3y+7=4y+7-2y | | 6y+2y=26 | | -3(4b-10)=12(24+60) | | sqrt(x)=13 | | 3(x+2)+2(x+4)=-1 | | 2(3+2x)+3(x-4)=8 | | 9(7x-3)=1+2x | | 2x^2+17x+10=0 | | -12=-12a | | 25x+15=24x+10 | | 2x+1/x-4=6 | | -q/5=30 | | 12-7x=2(18-9+3) | | 12-5x=2(18-9+2) | | 7+3x=6x-3 | | 7(x^3+x^2-4)=7x^3+8 | | 16-9x^2y^2=0 | | 8x+3/5=3x+9/3 | | 9/5x=21 | | 4x*9/7=0 | | 10r^2s^2+9rst+2t^2=0 | | -6q=-5q+7 | | 2ab(5a-7b)= | | x/2-x/3=5/6 |